Organotin 1996
DOI: 10.1007/978-94-009-1507-7_16
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of TBT by Aquatic Organisms

Abstract: Tributyltin (TBT) is accumulated by all taxa that have been examined. Typical tissue

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Fig. 3, thus, constitutes a prime confirmation of the contention by Laughlin (1996) that biomonitors likely reflect the steady-state distribution of TBT in all compartments of the ecosystem rather than the concentration in a single one.…”
Section: Bioaccumulationsupporting
confidence: 66%
“…Fig. 3, thus, constitutes a prime confirmation of the contention by Laughlin (1996) that biomonitors likely reflect the steady-state distribution of TBT in all compartments of the ecosystem rather than the concentration in a single one.…”
Section: Bioaccumulationsupporting
confidence: 66%
“…Most research on TBT accumulation by marine invertebrates was concentrated on mollusks (bivalves) and crustaceans (decapods), because these groups dominate the ecological habitat and serve as important seafood resources (Laughlin 1996). Research conducted on TBT accumulation by marine invertebrates revealed that marine bivalves are able to accumulate significant amounts of TBT (up to > 5 μg g -1 ) (Laughlin 1996).…”
Section: Bioaccumulation In Marine Invertebratesmentioning
confidence: 99%
“…Marine bivalves are also able to accumulate significant amounts of TBT (up to 5 μg g -1 ). But fish and crustaceans accumulate much lower amounts, owing to their possession of efficient enzymatic mechanisms to degrade TBT (Laughlin 1996). Absorption in mice is also low, and TBT is mainly excreted unchanged via the feces.…”
Section: Bioaccumulationmentioning
confidence: 99%
“…Actually, the transport of MeHg across cell membrane appears to be mediated by glutathione and other small mobile thiol ligands (Richardson & Murphy 1975, Ballatori 1991. Such a carrier-medlated transport is not known to occur with TBT (Laughlin 1996). A model developed instead for trialkyltin compounds is based on the passive diffusion of neutral species (Pelletier 1995, and references t h e r e~n ) .…”
Section: Absorption and Distributionmentioning
confidence: 99%